The Sinicization of jazz: Exploring the rise and fall of jazz cultures in Shanghai from the colonial to the communist eras - Chaichana, Tanarat (Humanities, Arts and Social Sciences Studies, 2024)
Compared with the numerous historical analyses of the development of jazz in the United States, few such accounts retell the history of jazz in Asia. Addressing this gap, this paper investigates the jazz culture of Shanghai between 1920 and 1950, drawing on records of foreign jazz musicians who traveled to Shanghai to perform and the academic literature on the development of jazz in Shanghai, with a primary focus on the contemporary social practice of jazz in Shanghai. Jazz culture entered Shanghai as a result of Western colonialism, prompting an influx of foreign musicians. The travel journals of international jazz performers Whitey Smith and Buck Clayton provide valuable documentation of two musicians who had a significant impact on Shanghai’s jazz culture. Another significant figure is Chinese musician Li Jinhui, a pioneer of “yellow music,” a hybrid genre combining features of jazz and Chinese folk songs. This music came to be considered “decadent sounds” and was banned in 1949 when the Chinese communist regime came to power, a moment perceived as marking a decline in Shanghai’s jazz culture. Yet with the introduction of the "Open Door Policy" in 1978, Shanghai witnessed a resurgence of jazz as restrictions on other cultures—particularly Western cultures—were eliminated. This paper demonstrates how Shanghai jazz developed from its early stages under the colonial economy to become a distinctive musical form that suited the tastes of the city’s audiences before disappearing due to political upheaval throughout the country.